KEUNGGULAN KOMPETITIF PRODUK TEPUNG KELAPA PADA PT. PUTRA KARANGETANG MINAHASA SELATAN - Amelia Prisilia Sarah Tombeng; Leonardus R. Rengkung; Nordy F. L. Waney (AGRI-SOSIOEKONOMI, 2018)
The purpose of this study to determine the competitive advantage of coconut flour products at PT. Putra of Karangetang as measured by Low Cost Strategy, Product Differentiation and FocusStrategy. Research conducted at PT. Putra Karangetang located in Popontolen Village, Tumpaan Sub-District, South Minahasa Regency, in March 2017 until May 2017. The data used are primarydata through direct interview and filling questionnaire with sampling using simple random sampling method as much as 30 respondents who bought the product in PT. Putra of Karangetang, South Minahasa. The data is measured using Likert scale. The results showed the process of measuring the competitive advantage of coconut flour products at PT. Putra Karangetang South Minahasa total data retrieval 1517 which shows the index rate measuring consumer satisfaction of 72.23% and quite satisfied. This indicates that the company in PT. Putra Karangetang Minahasa Selatan aware about the benefits of coconut flour products in PT. Putra of Karangetang seen from low cost strategy, product difference strategy, focus strategy.